Scientific Research Dilemmas - Arribalzaga, Eduardo (1997)
In the framework of scientific research, new dilemmas come from scientific-technologic advances. 'file objective of this paper is to define the appointment of research physician about these facts. A survey with 4 informative questions about update medicine, ethics and research between physicians of all specialities and medical students was sort; 286 of the 500 inquiries were analized. Only a difference according to preserving procedures of organs destined to transplants was seen: most of the physicians are in accord with preserving of organs by special techniques. Conversely, the undergraduates unknown the procedure to choice. With relation to the research papers, they must warrant the same ethic principles to those defined for all trials.